2023
DOI: 10.1108/jamr-04-2022-0087
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of logistics centers in terms of sustainability via MCDM methods

Abstract: PurposeThe purpose of the study is the evaluation of choosing the determined logistics centers’ (LCs’) locations via Multi-Criteria Decision-Making (MCDM) methods.Design/methodology/approachSince there is more than one criterion in the evaluation of LC location, MCDM methods are used. The Entropy and CRiteria Importance Through Intercriteria Correlation (CRITIC) methods are used to determine the main criteria and sub-criteria weights. The Preference Ranking Organization Method for Enrichment Evaluation (PROMET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Conversely, centers like Turkoglu/Kahramanmaras and Gokkoy/Balikesir demonstrated inefficiencies akin to previous studies [40,41], highlighting the imperative to rectify input redundancies for enhanced performance. On the other hand, the study emphasized Kayacik/Konya LC exhibited similar input redundancies, yet it was identified as a potential successful center in a study conducted by [42]. This evaluation took place before the center commenced operations, focusing solely on its sustainability potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, centers like Turkoglu/Kahramanmaras and Gokkoy/Balikesir demonstrated inefficiencies akin to previous studies [40,41], highlighting the imperative to rectify input redundancies for enhanced performance. On the other hand, the study emphasized Kayacik/Konya LC exhibited similar input redundancies, yet it was identified as a potential successful center in a study conducted by [42]. This evaluation took place before the center commenced operations, focusing solely on its sustainability potential.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed excess input factors in inefficient LCs and observed low cargo volume in these LCs. Assessing the performance rankings of LCs based on their potential efficiencies was conducted by Dumlu and Wolff [41] using the MOORA (Multi-objective Optimization by Ratio Analysis) method and by Keleş and Pekkaya [42] using the PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluation)-CRITIC (Criteria Importance Through Inter-criteria Correlation) approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The input parameter and assumption sensitivity can be limited in the study. Sustainability considerations were researched before deciding on a location for a logistics center [41]. The authors suggested improving decision-making using an ordered weighted average (OWA) operator and a similarity based TOPSIS technique.…”
Section: Geographic Informationmentioning
confidence: 99%
“…The study suggested using renewable energy to improve the sustainability of the targeted plants. Keles ¸and Pekkaya (2023) prioritize the sustainable performance of 12 Turkish logistical centers. CRITIC was employed in the study to provide weightage to the 12 sustainability criteria.…”
Section: Prioritizing the Attributesmentioning
confidence: 99%
“…Keleş and Pekkaya (2023) prioritize the sustainable performance of 12 Turkish logistical centers. CRITIC was employed in the study to provide weightage to the 12 sustainability criteria.…”
Section: Literature Reviewmentioning
confidence: 99%